The Relationship between Vitamin D and Autism Spectrum Disorder - Budi Kristianto; Nining Febriyana; Royke Tony Kalalo (HM Publisher, 2021)
The tendency for autism spectrum disorders or also known as Autism Spectrum Disorder (ASD) is increasing globally, even becoming 1 per 54 in 2016. Until now, the cause of autism is not known for certain, ASD is considered to be a combination of genetic and environmental factors. One of the environmental factors in this case is related to nutrition, one of which is vitamin D. Vitamin D deficiency is often found among children with ASD. Several studies have shown that vitamin D is involved in various brain bioprocesses including neuromodulation and nerve transmission and brain function while also influencing inflammatory processes, autoimmune disorders, oxidative stress and also neurotransmitters that are widely associated with the possibility of ASD. This review aims to describe vitamin D deficiency may contribute to ASD disorders. Based on this, in the future, it is necessary to consider when treating patients with ASD to consider the need to check the patient's vitamin D levels and if there is a deficiency it can be advised to sunbathe and or be given additional vitamin D intake.